Typical Characteristics of German Speech and Oral Discourse - Berdimurodov Adham Musurmonovich (Zien Journals, 2022)
The article provides information and recommendations on the typical characteristics of a German speaking discourse and its specifics. You can also see a list and descriptions of words that are currently widely used in German speech.
Keywords: assimilation; category; layer; sheet